The Role of Satisfaction in Enhancing Customer Loyalty in Islamic Mobile Banking Services of Bank Syariah Indonesia - Miftahul Rachma; J. Junaidi; Suhardi M. Anwar (Manunggal Halim Jaya, 2026)
This study aims to address the research question of how perceived security, perceived ease of use, and service facilities influence customer loyalty toward Islamic mobile banking services, both directly and indirectly through trust and satisfaction. Specifically, this study tests the hypotheses that perceived security and perceived ease of use positively affect customer loyalty among BSI Mobile users. That trust and satisfaction mediate these relationships, while the effect of service facilities is expected to be more prominent through customer satisfaction. An explanatory quantitative approach was employed, collecting data from 240 active users of BSI Mobile, which were analyzed using Structural Equation Modeling (SEM) in AMOS. The results indicate that perceived security and perceived ease of use have positive and significant effects on both trust and satisfaction. In contrast, service facilities do not have a significant effect on trust but do have a positive, significant effect on customer satisfaction. Furthermore, trust and satisfaction are proven to have significant positive effects on customer loyalty, with satisfaction emerging as the most dominant mediating variable in the structural model. These findings provide more profound insight: customer loyalty in Islamic mobile banking is shaped more by satisfaction with secure, user-friendly digital experiences than by the mere availability of service features. Theoretically, this study extends the Technology Acceptance Model (TAM) by integrating the dual mediating roles of trust and satisfaction in the context of Islamic banking. Practically, the findings emphasize the importance of Islamic banks' digital transformation strategies that prioritize system security and user experience optimization to foster sustainable customer loyalty and strengthen public trust in a Sharia-compliant digital financial ecosystem.